Eksotika Lee Man Fong : Sebuah Kolaborasi Apik Seni Rupa Modern dan Seni Lukis Tradisi China - Satrio Hari Wicaksono (Institut Seni Indonesia Yogyakarta, 2017)
In the development of Indonesian art, many artists who then fill out the history of the art of this country with a wide range of distinctive characteristics as a statement of the identity of the artist in his work, not to mention Lee Man Fong. Characteristics that are present in his work is a new breakthrough that combines the character of modern Western art with Eastern art, particularly China. A different viewpoints but can be combined and harmonized beautifully by the artist. With the approach does, Lee Man Fong able to get admission in the middle of rampant identity themes that are starting to be an important theme in the struggle of Indonesia. While many doubted the sense of nationalism, because the themes present in his work is more about the daily life and explores the theme instead filled with the spirit of struggle, but the emotional intimacy that is present in his work is able to capture the reality of the life of the Indonesian people that might escape from the views of many. A manifestation of the artist's love of the little things around it. Didn’t many artists are able to portray himself as a strong identity in his work, but Lee Man Fong's capacity and unique views will present a new visual way to penetrate the sustainability of Indonesian art that has evolved during that time. The use of methods, techniques, perspectives, and understanding which is a collaboration between the schools of modern and classic is the force that makes Lee Man Fong became one of the distinguishing elements. An approach that provides a fresh new look and adds such a richness of Indonesian art.